Effect of maternal pre-pregnancy body mass index and gestational weight gain on birth weight and gestational age: An observational cross-sectional study - Shaon Mitra; Arnab Mondal (Asian Journal of Medical Sciences, 2024)
Background: Studies show that pre-pregnancy body mass index (ppBMI) and gestational weight gain (GWG) are associated with birth weight (BW), gestational age (GA), and neonatal morbidities. Higher BW leads to metabolic syndrome. Preterm and low BW (LBW) have short and long-term morbidities. Monitoring ppBMI and GWG is necessary as these are modifiable risk factors for obesity. In this study, we revisited these findings in an Indian scenario.